1999
DOI: 10.1023/a:1008950210967
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: These complex patterns defy easy generalization and illustrate why US cancer data should be stratified by socioeconomic position, along with race/ethnicity and gender, so as to improve cancer surveillance, research, and control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
55
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(65 citation statements)
references
References 26 publications
10
55
0
Order By: Relevance
“…First, it may be that non-metropolitan doctors for low-SES mothers are more likely than doctors of high-SES mothers to view the daughters of these women as having greater risk for contracting HPV due to relatively younger ages at first sexual intercourse and greater likelihood of sexual risk-taking among low-SES girls, especially in rural areas [3, 14]. They may therefore be more likely to recommend vaccination for those girls.…”
Section: Discussionmentioning
confidence: 99%
“…First, it may be that non-metropolitan doctors for low-SES mothers are more likely than doctors of high-SES mothers to view the daughters of these women as having greater risk for contracting HPV due to relatively younger ages at first sexual intercourse and greater likelihood of sexual risk-taking among low-SES girls, especially in rural areas [3, 14]. They may therefore be more likely to recommend vaccination for those girls.…”
Section: Discussionmentioning
confidence: 99%
“…A recently presented abstract has demonstrated that women with low SES and ovarian cancer were less likely to receive primary surgery or chemotherapy [44]. The absence of socioeconomic data in disparity research is problematic as it can lead to the reification of race [45].…”
Section: Discussionmentioning
confidence: 99%
“…22 Evidence shows that racial and ethnic factors may increase the risk of medical illness. It is widely reported 7375 that certain medical conditions or diseases are more prevalent in particular ethnic communities. For example, minorities and immigrants often have more complicated medical problems, which may not respond easily to standard treatment regimens.…”
Section: Developing a Disparities Agenda In Sleep Medicinementioning
confidence: 99%